The "States" of Newborn Screening. Issue 6 (November 2017) - Anderson, Sharon
Abstract : Nurses and providers at all levels of practice must be well-informed about conditions that are screened on state-based newborn screening panels so they can provide accurate education and information to parents, and when necessary, facilitate timely referral.